Kajian Penerapan Stop Work Authority Terhadap First Aid Case Untuk Nol Lost Time Injury - Girman Sihombing (IMTechno: Journal of Industrial Management and Technology, 2022)
Safety and health in workplace is one of the main issues that must be considered in running company’s activities with the humanity, economic and regulation reason. By those reasons the companies will be motivated to make a safe work environment. Beside as a compliment to above reasons, the commitment, and a proof of zero lost time injury (LTI) will strengthen business competitiveness, because some work agreements among companies have been based on the requirement of work health and safety system application (SMK3). Generally, many ways in getting SMK3 good work performance, for example the application of stop work authority (SWA) if the activities have a potential hazard, safety card if there is a potential hazard in working area, Job safety observation and the others. This research takes the application of SWA and its influence on the amount of first aid case. According to Frank Bird’s theory which is known as accident pyramid, the more near miss happened, the more first aid cases, facilities damages, and fatalities. Stop work authority is hoped to minimize or to eliminate the first aid case so that no lost time injury.